"Blockchain‐Like" MIL‐101(Cr)/Carbon Black Electrodes for Unprecedented Defluorination by Capacitive Deionization. Issue 10 (20th December 2022) - Yu, Fei; Zhang, Xiaochen; Liu, Peng; Chen, Bingbing; Ma, Jie
Abstract: Metal‐organic frameworks (MOF) have attracted extensive attention due to their ultra‐high specific surface area and tunable structure, the mechanism of direct utilization for capacitive deionization (CDI) defluorination remains undefined. Here, MIL‐101(Cr) with ultra‐high specific surface area, high water stability, and open metal sites (OMSs) is prepared by a hydrothermal method for defluorination of CDI. Carbon black is used as a "chain" to connect F‐stored in the holes of MIL‐101(Cr) (Cr‐MOF)as "blocks" to enhance the conductivity and ion storage capacity of MIL‐101(Cr)/carbon black electrodes (Cr‐MOF electrodes). This simple construction method avoids the process complexity of in situ synthesis and performs better. These easily constructed "blockchain‐like" Cr‐MOF electrodes exhibit excellent defluorination capacity (39.84 mgNaF gelectrodes −1 ), low energy consumption (1.2 kWh kgNaF −1 ), and good stability. The coupling of the electrochemical redox reaction of Cr 3+ /Cr 4+ with confined water is investigated using in situ and ex situ analysis methods combined with density functional theory (DFT), resulting in an unprecedented defluorination mechanism for Cr‐MOF electrodes. This study opens up new ideas for the application of MOF in CDI, clarifies the removal mechanism of MOF, and lays a foundation for further promoting the application of raw materials with poor conductivity in the field of CDI. Abstract : Carbon black is used as a "chain" to connect fluoride ions stored in the holes of MIL‐101(Cr) as "blocks" to enhance the conductivity and ion storage capacity of electrodes. These easily constructed "blockchain‐like" MIL‐101(Cr)/carbon black (Cr‐MOF) electrodes exhibit excellent defluorination capacity, low energy consumption, and good stability. This study promotes the application of raw materials with poor conductivity in the field of capacitive deionization (CDI).